2019
DOI: 10.1016/j.foodqual.2019.01.016
|View full text |Cite
|
Sign up to set email alerts
|

The influence of oral lubrication on food intake: A proof-of-concept study

Abstract: As overeating, overweight and obesity remain public health concerns, it is crucial to design satiety-enhancing foods that suppress appetite and lower snack intake. Existing research identifies oro-sensory targets to promote satiation and satiety, yet it remains unclear as to whether it is 'chewing' or 'oral lubrication' that might amplify satiation signals. In this study, techniques from experimental psychology, food material science and mechanical engineering have been combined to develop model foods to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…Many included studies adopted a within-subject design, with the exception of three which used a between-subject design 29 , 50 , 51 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many included studies adopted a within-subject design, with the exception of three which used a between-subject design 29 , 50 , 51 .…”
Section: Resultsmentioning
confidence: 99%
“…hydrocolloid based gels with various inclusions to create different levels of textural complexity or in other words higher degree of heterogeneity and assess the relationships between the gels and satiety. Besides classical rheological measurements, McCrickerd et al (2014) 28 and Krop et al (2019) 29 measured the lubricity of foods without or with simulated saliva (food boli i.e. food and simulated saliva mixture), respectively, using a Mini Traction Machine tribometer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, recent studies have demonstrated correlation between the tribological performance of edible hydrogels in soft silicon contacts with oral perception attributes, such as pastiness and slipperiness 8 and effects of such unique lubrication on satiety responses. 9 Aqueous lubrication has been recognized as one of the main mechanisms for bio-lubrication due to the abundance of water in complex living organisms. 10 Aqueous lubrication is attributed to the capacity of biopolymers to electrostatically bind water molecules while being tethered to the bio-surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, food gels increasingly come with performance comparable to, and in some cases greater than, synthetic polymer gels owing to specific structuring and processing mechanisms typical of these systems [13][14][15][16] . Food gels also play a critical role in modern food design, such as in structuring foods with desired sensorial textures 17 , preserving metastable food structures and increasing shelf-life 18,19 , replacing fats 20 , enhancing satiety by reducing food intake [21][22][23] and in the design of complex food shapes via three-dimensional (3D) printing 24 . The appropriate design of food gels can not only improve food quality, but also improve nutrition and bioavailability features of foods [25][26][27] .…”
mentioning
confidence: 99%